The split common null point problem and the shrinking projection method in Banach spaces. (1st February 2016) - Takahashi, Satoru; Takahashi, Wataru
Abstract : In this paper, we consider the split common null point problem with resolvents of maximal monotone operators in Banach spaces. Then, using the shrinking projection method, we prove a strong convergence theorem for finding a solution of the split common null point problem in Banach spaces.